Exploring consumers’ perceptions of online purchase decision factors: electroencephalography and eye-tracking evidence - Pšurný, Michal; Mokrý, Stanislav; Stavkova, Jana (Frontiers in Human Neuroscience, 2024)
Consumer behavior on the Internet is influenced by factors that can affect consumers' perception and attention to products. Understanding these processes at the neurobiological level can help to understand consumers' implicit responses to marketing stimuli. The objective of this study is to use electroencephalography (EEG) to investigate the differential effects of selected online purchase decision factors that are becoming increasingly important in online shopping. Using event-related potentials (ERPs) and simultaneous eye-tracking measurements, we identified differences in the perception of utilitarian and hedonic products when the products are exposed together with visual elements of the factors review, discount, and quantity discount. The ERP analysis focused on the P200 and LPP components. By freeviewing the stimuli during the measurement, early automatic and later more complex attentional affective responses could be observed. The results suggest that the review and discount factors are processed faster than the product itself. However, the eye-tracking data show that the brain processes the factor without looking at it directly, i.e., from a peripheral view. The paper also demonstrates the possibilities of using new objective methods based on neurobiology and how they can be applied, especially in areas where the use of neuroscience is still rare, yet so much needed to objectify consumers' knowledge of their need satisfaction behavior.